Development Of A Competency Model For Millennial Noken Crafters To Enhance The Competitive Advantage Based On The Creative Economy In The City Of Jayapura - Leon Mitra Harju2; Isma Shalihi Ahlia; Fanny Kristin Tantyah Sitompul; Iriando Wijaya; Adriel Sitompul (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study examines the competencies of millennial noken crafters in Jayapura City to improve competitive advantages based on the creative economy. The research design uses a mixed method with an Explanatory Sequential Design approach. Quantitative data was collected through a survey of 27 noken crafters with data analysis using Exploratory Factor Analysis (EFA) and multiple regression. Qualitative data was collected through in-depth interviews, observations, and document studies. The results show that the competence of noken craftsmen is largely determined by attitudes and values (β=0.403), while the competitive advantage of noken is determined by product differentiation (β=0.430). The most dominant aspect of the creative economy is the ability of noken crafters to access markets and marketing (β=0.321). Qualitative analysis highlights the need for technical training, strengthening cultural values, design differentiation, consistent promotion, and the role of government support. The competency model developed is the result of integrating attitudes and values, knowledge, and skills, then linking them to markets and marketing, creativity and innovation, collaboration and policy, cultural added value, quality and consistency to strengthen the competitiveness and sustainability of noken businesses in the creative economy era. This model is expected to serve as a practical guideline for the development of millennial noken crafters in Jayapura.